Community Empowerment Program in Indonesia - Farida, Umi; Qabandiya, Muh Kholidinna (Cendekiawan Indonesia Timur, 2022)
Development is an effort to increase the dignity of those people who, in their condition, are unable to escape from the trap of poverty and underdevelopment. In the context of efforts to manifest the success of development in the Mamuju Regency, it is necessary to choose paradigms and strategies used as the basis for the development process.